Development of an HPLC/DAD method for determination of phenolic profile in portuguese olive fruits - Ferreira da Vinha, Ana (2021)
Polyphenolic compounds inliuence the sensorial properties of olive fruits and virgin olive oils and are imporlant markers for studying fruit characteristics of different cultivars and for controlling oil production processes . A few chromatographic methods have been used to study the phenolic compounds of olive fruit . This communication reports the development of a new HPLCIDAD methodology to separate, identify aml quanlily lhe phenolic compounds from Portuguese olive fruit cultivars (Cobrançosa, Madura/and Verdeal).